2020
DOI: 10.1590/0100-3984.2018.0075
|View full text |Cite
|
Sign up to set email alerts
|

Main complications of hip arthroplasty: pictorial essay

Abstract: Hip arthroplasty is a widely used and successful orthopedic procedure for the treatment of degenerative, inflammatory, or traumatic joint disease. The procedure promotes significant pain relief, as well as recovery of limb function, reduction of disability, and better quality of life. However, there are related complications, which have characteristic imaging aspects. In the present study, we review the literature and exemplify such complications using images obtained at our facility, illustrating the main rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
8
0
3
Order By: Relevance
“…Longo and Koeneman [ 29 ] predicted that radiography, to date the most utilized technique for the non-destructive examination of conventional metallic implanted orthopaedic prostheses [ 30 ], would become a powerful in vitro and/or in vivo technique to detect and characterize minor changes of the structural integrity of complex composite implanted prostheses; however, the state of art has shown that this goal has not been achieved, despite the huge potential offered by X-rays to monitor with unbeatable accuracy the damage initiation and progression in this class of materials under dry environments [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longo and Koeneman [ 29 ] predicted that radiography, to date the most utilized technique for the non-destructive examination of conventional metallic implanted orthopaedic prostheses [ 30 ], would become a powerful in vitro and/or in vivo technique to detect and characterize minor changes of the structural integrity of complex composite implanted prostheses; however, the state of art has shown that this goal has not been achieved, despite the huge potential offered by X-rays to monitor with unbeatable accuracy the damage initiation and progression in this class of materials under dry environments [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longo and Koeneman [29] predicted that radiography, to date the most utilized technique for the non-destructive examination of conventional metallic implanted orthopaedic prostheses [30], would become a powerful in vitro and/or in vivo technique to detect and characterize minor changes of the structural integrity of complex composite implanted prostheses; however, the state of art has shown that this goal has not been achieved, despite the huge potential offered by X-rays to monitor with unbeatable accuracy the damage initiation and progression in this class of materials under dry environments [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…[5,7]. As the procedure-specific factors, acetabular cup diameter, femoral head diameter, femoral neck length, head-to-cup ratio, procedure type, and the use of a liner were analyzed [8]. Although treatment outcome highly depends on the quality of surgical reconstruction of anatomical and biomechanical relations of the bone tissue [3], HD was noticed to occur even in the absence of procedure-specific mistakes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, patientspecific risk factors for HD, including advanced age, high body mass index, comorbidities (especially psychiatric and neurologic diseases), low physical activity level, preoperative use of walking aids (PUWA), impaired compliance (failure to comply to permitted activities after surgery), and absence of exercise therapy, were suggested as important [7,9,10,11]. According to the most recent studies, the length of stay (LOS) after THA has been shortened [4,7,8]. Out of many different patients' and providers' characteristics that determine LOS, comorbidity is the most documented one [12,13].…”
Section: Introductionmentioning
confidence: 99%